Best practice guidance for inclusive digital tool development for sustainable rice in Vietnam - Nelson, Katherine; Barnard, Jennifer; Vu Hong Trang (International Rice Research Institute, 2022)
This brief summarizes findings of the project “Agroecological transitions for building resilient and inclusive agricultural and food systems” (TRANSITIONS), which is funded by the European Commission through its DeSIRA initiative and managed by the International Fund for Agricultural Development (IFAD). The Digital Tools regional work in Vietnam focused on research and engagement with digital tools for technical advice and performance assessment in sustainable rice production in the Mekong River Delta. This best practice guidance was developed based on findings from a review of existing digital tools for the rice value chain in Vietnam, a baseline survey with rice farmers and extension workers and a participatory dialogue with relevant stakeholders on the challenges of reaching Vietnamese smallholder rice farmers with digital tools.